Vocal Learning Revolution: Student Preferences in The Digital Platform Era - Rahmatunnisa Ramadhani S; Uus Karwati; Diah Latifah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to investigate students’ preferences for digital platform features in vocal learning, examine the factors influencing those preferences, and explore their associations with learning motivation and learning outcomes. A quantitative cross-sectional survey design was employed involving 384 university students actively engaged in digital-based vocal learning. Data were collected through structured questionnaires, the construct validity of which was confirmed using confirmatory factor analysis (CFA). The data were subsequently analyzed using descriptive statistics and inferential techniques, including independent-samples t-tests, one-way ANOVA, Pearson correlation analysis, and multiple regression analysis. The findings revealed that audio-visual features received the highest preference rating (M = 4.32, SD = 0.68), followed by real-time feedback (M = 4.28), accessibility (M = 4.21), content personalization (M = 4.15), discussion forums (M = 3.97), and gamification (M = 3.89). Education level (F = 5.83, p = .003) and digital skill proficiency (F = 12.67, p < .001) significantly influenced students’ preferences, whereas gender showed no statistically significant difference (t = 1.42, p = .157). Furthermore, platform preferences demonstrated significant positive correlations with learning motivation (r = 0.52, p < .001) and learning outcomes (r = 0.41, p < .001). These findings provide practical implications for platform developers and educators in designing student-centered vocal learning environments that are responsive to contemporary learners’ needs.